Analysis of chemical and sensory characteristics of sapodilla dodol with various formulations of glutinous rice flour - Linangsari, Titis; Hasanah, Uswatun (Journal of Food and Agricultural Product, 2024)
Sapodilla has not been widely utilized as a processed food product. The processing of sawo into sawo dodol is expected to increase the added value of sawo fruit. The purpose of this study was to analyze the chemical characteristics and the panelists' acceptance of dodol with various formulations of the addition of glutinous rice flour. The method used in making sapodilla dodol is experimental with a comparison of the use of glutinous rice flour, namely F1 (50 gr), F2 (100 gr), F3 (150 gr) and F4 (200 gr). The tests carried out were chemical tests (water content test, ash content test, fat content test and protein test) as well as organoleptic tests (hedonic test). The results showed that the results of the moisture content test had a value of 21.25%-28.86%, the ash content test had a value of 0.91-1.13%, the fat content test had a value of 7.03%-14.39 and the protein has a value range of 1.67% -2.23%. Moisture content and protein content did not meet SNI 01-2986-1992, while ash content and fat content complied with SNI 01-2986-1992 and F4 which formulation was the most preferred by the panelists, namely the formulation with the addition of 200 grams of glutinous rice flour. Keywords: characteristic, chemical, dodol, sapodilla, sensory